2001
DOI: 10.1097/00003246-200112000-00013
|View full text |Cite
|
Sign up to set email alerts
|

Apoptosis in cells of bronchoalveolar lavage: A cellular reaction in patients who die with sepsis and respiratory failure

Abstract: The prolonged survival of lung cells in septic patients and especially of alveolar macrophages may be attributable to the inhibition of apoptosis. This seems to represent an initial attempt of the host to increase the defense capacity to kill the invading microorganism, resulting in an unbalanced tissue load of cells and an uncontrolled release of toxic metabolites. Furthermore, the inhibition of apoptosis in septic patients may explain why lung function is impaired, leading to sepsis-induced acute respiratory… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
13
0
1

Year Published

2003
2003
2015
2015

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 19 publications
(16 citation statements)
references
References 39 publications
2
13
0
1
Order By: Relevance
“…Therefore, a vicious circle may be in place during human ARDS. Further investigations are required Lastly, we searched for IFN-γ secretion, as it is known to be synthesized in the alveolar space [6][7][8][9], and also because the Th17 pathway is inhibited by IFN-γ [23]. Accordingly, our results suggest that IL-17 and IFN-γ were not concomitantly secreted by alveolar T-cells in humans (see Fig.…”
Section: Discussionmentioning
confidence: 93%
See 1 more Smart Citation
“…Therefore, a vicious circle may be in place during human ARDS. Further investigations are required Lastly, we searched for IFN-γ secretion, as it is known to be synthesized in the alveolar space [6][7][8][9], and also because the Th17 pathway is inhibited by IFN-γ [23]. Accordingly, our results suggest that IL-17 and IFN-γ were not concomitantly secreted by alveolar T-cells in humans (see Fig.…”
Section: Discussionmentioning
confidence: 93%
“…During ARDS, an accumulation of polymorphonuclear neutrophils (PMN) and alveolar macrophages (AM) occur in the alveolar spaces, which is linked to both an increase in their recruitment and an inhibition of cellular apoptosis [5][6][7][8][9]. This activation of innate immunity takes place rapidly, which is being considered as the first line of defense in the lungs [9].…”
Section: Introductionmentioning
confidence: 99%
“…We have determined that collectins enhance the pinocytosis and phagocytosis of DNA by macrophages (33,34), and these findings will be described in detail elsewhere. 2 Common inflammatory disease/conditions such as septic shock (44), chronic obstructive pulmonary disease, and asthma contain impaired surfactant and increased amounts of apoptotic cells, cellular debris, and secretions in their airways. Interestingly, Pseudomonas aeruginosa secretes DNA, particularly into the lung environment of cystic fibrosis (CF) patients to form a coat of biofilm to establish persistent infection (2), and innate immune proteins are primarily responsible for clearing these pulmonary infections (3).…”
Section: Discussionmentioning
confidence: 99%
“…It is also known that increased concentrations of free DNA in the lung cause inflammation and septic shock during gene therapy experiments (47) in addition to the disease conditions (9,44,48). Because our results show that the innate immune collectins bind both bacterial and host genomic DNA (Figs.…”
Section: Discussionmentioning
confidence: 99%
“…Several groups of investigators have demonstrated that cultured cells undergo apoptosis following exposure to hyperoxia. 21 Although, it represents a physiologic clearance mechanism in human tissues, 22 apoptosis of neurons and glia contribute to the overall pathology of traumatic brain injury in both humans and animals. In both head-injured humans and following experimental brain injury, apoptotic cells have been observed alongside degenerating cells exhibiting classic necrotic morphology.…”
Section: Discussionmentioning
confidence: 99%